Review of corrosion monitoring and prognostics in offshore wind turbine structures: Current status and feasible approaches - Brijder, Robert; Hagen, Catalina H. M.; Cortés, Ainhoa; Irizar, Andoni; Thibbotuwa, Upeksha Chathurani; Helsen, Stijn; Vásquez, Sandra; Ompusunggu, Agusmian Partogi (Frontiers in Energy Research, 2022)
As large wind farms are now often operating far from the shore, remote condition monitoring and condition prognostics become necessary to avoid excessive operation and maintenance costs while ensuring reliable operation. Corrosion, and in particular uniform corrosion, is a leading cause of failure for Offshore Wind Turbine (OWT) structures due to the harsh and highly corrosive environmental conditions in which they operate. This paper reviews the state-of-the-art in corrosion mechanism and models, corrosion monitoring and corrosion prognostics with a view on the applicability to OWT structures. Moreover, we discuss research challenges and open issues as well strategic directions for future research and development of cost-effective solutions for corrosion monitoring and prognostics for OWT structures. In particular, we point out the suitability of non-destructive autonomous corrosion monitoring systems based on ultrasound measurements, combined with hybrid prognosis methods based on Bayesian Filtering and corrosion empirical models.